Communication intelligence leverage your strengths and optimize every interaction to work best with others - Morgan, Claude D'Val (McGraw Hill-Ascent Audio, 2023)
Now, more than ever, Communication Intelligence is essential for workers at all levels. The good news is that you can learn to develop and master this vital competency. If you're interested in being your best through effective communication, that's exactly what you will find in this book. With more than four decades of study, research, and coaching in the field, C.D. "Hoop" Morgan III has built on the original premise of The Forte Institute: That assessing an individual's communication style should start with a focus on their strengths-not their weaknesses. Communication Intelligence guides you to identify your unique strengths based on the Forte Communication Style Profile and will help you discover: your personalized communication strengths-the first step on the road to Communication Intelligence mastery; how you're currently adapting in your workspace and how you're "most likely" coming across to others; and how to understand others' communication style preferences and strengths to communicate even more effectively, and more. In this book, you will learn how to adapt and understand how others perceive you while being introduced to the ten CQ essential attributes and dozens of strategies and tips to build on your strengths to enhance your Communication Intelligence
Online resource; title from title details screen (O'Reilly, viewed July 11, 2023)
Keywords: Communication in organizations; Communication in management; Interpersonal communication; Communication dans les organisations; Communication en gestion; Communication interpersonnelle; Audiobooks; Livres audio